1974
DOI: 10.1002/art.1780170415
|View full text |Cite
|
Sign up to set email alerts
|

Experimental gouty synovitis caused by bacterial endotoxin adsorbed onto urate crystals

Abstract: We used a laboratory model of gouty synovitis giving quantitative dosedependent results with urate injection intrasynovially into the knee joint of dogs. We found that when precautions were taken to prevent any possible endotoxin contamination of the urate crystals, they became significantly less active. Endotoxin by itself, from Escherichia coli, was very potent in causing pain and leukocytic infiltration into the knee joint. Such endotoxin was readily and firmly adsorbed onto urate crystals. A small dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Phelps and McCarty have found that MSU crystals heated at 200°C for 2 hours no longer activated complement (7), presumably due to the removal of pyrogens from the crystalline surfaces (8). Naff and Byers also noted that heated crystals no longer activated complement but, when heated crystals were dissolved and recrystallized, they regained their ability to deplete complement activity (9).…”
Section: Structural Changes In Sodium Urate Crystals On Heating Neil mentioning
confidence: 99%
“…Phelps and McCarty have found that MSU crystals heated at 200°C for 2 hours no longer activated complement (7), presumably due to the removal of pyrogens from the crystalline surfaces (8). Naff and Byers also noted that heated crystals no longer activated complement but, when heated crystals were dissolved and recrystallized, they regained their ability to deplete complement activity (9).…”
Section: Structural Changes In Sodium Urate Crystals On Heating Neil mentioning
confidence: 99%
“…The provocation of acute gout by infection or by the intravenous injection of bacterial pyrogen (Sicuteri 1968) led Van Arman et al (1974) to examine the effect of injecting into the joints of dogs urate crystals on to the surface of which had been absorbed endotoxin obtained from Escherichia coli. Such crystals produced a more severe synovitis than crystals free of endotoxin.…”
Section: Endotoxinsmentioning
confidence: 99%
“…Quantitatively the differences in purity might be only small, but qualitatively (as for example with a pyrogenic contaminant) the practical consequences may be far from small. This has been clearly documented by Van Arman et al in their studies of the effects of minute amounts of endotoxins on the oedemagenic/algesic activity of sodium urate crystals [1].…”
Section: First Caveat: Purity and Reproducibility Of The Inflammatorymentioning
confidence: 85%